Valores de la identidad cultural en la escuela - Tacuri Jacome, Viviana Marisol (2023)
The objective of this research was to identify the values of cultural identity in the teaching-learning process in fifth grade students of the educational unit of the province of Cotopaxi, through a thorough investigation, in order to raise awareness and encourage them to maintain their ancestral cultures. Cultural values are those that represent a set of beliefs, languages, customs, traditions, and relationships that identify roots of different ethnic groups when participating in different activities and within the social skills we can say that they are behavioral strategies, capabilities to apply such behaviors that help us to solve a social situation. It is quantitative research since statistical data were used to reach a conclusion, also the deductive method was used. In addition, the project explores important topics such as: culture, identity, cultural identity values and cultural identity values in the EAP and their importance. Since, this information will facilitate the scope of a direct impact on the potentialities of society to improve coexistence in the educational community and in turn will improve the attitudes of each of the students.